2006
DOI: 10.1007/s00105-004-0890-5
|View full text |Cite
|
Sign up to set email alerts
|

Seltene Vaskulitiden als Hinweis auf Plasmozytom

Abstract: We report on two female patients who presented with painful recurrent palpable purpura, ulcers and necroses on the extremities. The results of all examinations and laboratory tests considered together suggested a diagnosis of necrotizing leukocytoclastic vasculitis. Leukocytoclastic vasculitis is an inflammatory necrotizing condition of the superficial dermal vessels, presenting with variable clinical symptoms. In most cases it becomes manifest as palpable purpura, but hemorrhagic-necrotizing, bullous, nodular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…In addition, the prognosis was favorable, and lesions healed after the institution of appropriate treatment: chemotherapy in 10 cases and 1 case after bone marrow transplant [ 2 , 4 , 11 , 14 25 ]. Two patients died before recovering, and there were no references in 9 cases [ 4 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prognosis was favorable, and lesions healed after the institution of appropriate treatment: chemotherapy in 10 cases and 1 case after bone marrow transplant [ 2 , 4 , 11 , 14 25 ]. Two patients died before recovering, and there were no references in 9 cases [ 4 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[25] There have been case reports of MM which described rare presentation as LCV. [67] In fact, in a study of 2357 patients with diagnosis of MM, only eight patients were found to have LCV. [8] It indicates a sign of poor prognosis with short survival rate which happened in our case also.…”
Section: Discussionmentioning
confidence: 99%
“…This vasculitis is an inflammatory necrotizing condition of the superficial dermal vessels, and is characterized by neutrophilic, angiocentric, segmental inflammation with endothelial cell injury and fibrinoid necrosis of the blood vessel walls [9]. Clinical symptoms are variable and include palpable purpura, and hemorrhagic-necrotizing, bullous, nodular, and urticarial lesions [10]. …”
Section: Discussionmentioning
confidence: 99%